What is the Role of Sustainability in the Relationship between Green Transformational Leadership and Firm Performance? - ALAY, hazal koray; keskin, abdulkadir; şen, gülaçtı; taksi deveciyan, meri (International Journal of Contemporary Economics and Administrative Sciences, 2024)
The aim of the research is to understand the relationship between green transformational leadership and firm performance, evaluating the role of sustainability strategies in this connection. Increasing global environmental issues and social inequalities necessitate companies to prioritize sustainability principles not only for financial concerns but also because of green transformation. In this context, focusing on the role of sustainability strategies is the main objective of the research. Quantitative research methods, specifically the cross-sectional survey method, were employed for data collection and analysis. A sample of 391 white-collar employees working in companies operating in Turkey was determined using the convenience sampling method. The data collected through surveys were analyzed using the AMOS 24 statistical program. The findings indicate that green transformational leadership is influential on firm performance, environmental sustainability, and economic sustainability. Additionally, economic sustainability was found to play a mediating role in the relationship between green transformational leadership and firm performance. It is expected that the obtained findings will provide a significant foundation for business leaders, guiding them in the development of sustainability-based strategies.